Analysis of Determinants of Quality of Life in Pulmonary TB Patients - Tasya Ariska; Asnawi Abdullah; Fahmi Ichwansyah; Hermansyah Hermansyah; Maidar Maidar (Indonesian Journal of Global Health Research, 2025)
Pulmonary Tuberculosis (TB) is one of the infectious diseases that often becomes a problem and the leading cause of death in the world. Improving the quality of life of TB patients is something that needs to be developed. Because quality of life is essential to support human life. To achieve a good quality of life, it is necessary to know more precisely the determinants of the quality of life of TB patients. This study aims to determine the determinants of the quality of life in TB patients in Banda Aceh City. This study is descriptive and analytical with a cross-sectional study design. The population is all TB patients in 4 working areas of the Health Center in Banda Aceh City. A sample of 57 people was taken using the total sampling technique. Data was collected in July 2023 by interviewing using a questionnaire—data analysis using logistic regression. The study showed that 30 of 57 TB patients (58.82%) had a good quality of life. Factors related to the quality of life of pulmonary TB patients are age (OR=1.08; 95%CI=1.75-71.64; p=0.002), income (OR=16.50; 95%CI=3.81-71.46; p=0.0001), duration of treatment (OR=31.90; 95%CI=3.64-279.29; p=0.002), family support (OR=38.00; 95%CI=6.87-120.05; p=0.0001), health literacy (OR=20.80; 95%CI=4.86-89.10; p=0.0001), and religious coping (OR=30.00; 95%CI=6.34-141.95; p=0.0001).